Intrinsic features of the cancer cell as drivers of immune checkpoint blockade response and refractoriness - Ursino, Chiara; Mouric, Cécile; Gros, Laurent; Bonnefoy, Nathalie; Faget, Julien (Frontiers in Immunology, 2023)
Immune checkpoint blockade represents the latest revolution in cancer treatment by substantially increasing patients’ lifetime and quality of life in multiple neoplastic pathologies. However, this new avenue of cancer management appeared extremely beneficial in a minority of cancer types and the sub-population of patients that would benefit from such therapies remain difficult to predict. In this review of the literature, we have summarized important knowledge linking cancer cell characteristics with the response to immunotherapy. Mostly focused on lung cancer, our objective was to illustrate how cancer cell diversity inside a well-defined pathology might explain sensitivity and refractoriness to immunotherapies. We first discuss how genomic instability, epigenetics and innate immune signaling could explain differences in the response to immune checkpoint blockers. Then, in a second part we detailed important notions suggesting that altered cancer cell metabolism, specific oncogenic signaling, tumor suppressor loss as well as tight control of the cGAS/STING pathway in the cancer cells can be associated with resistance to immune checkpoint blockade. At the end, we discussed recent evidences that could suggest that immune checkpoint blockade as first line therapy might shape the cancer cell clones’ diversity and give rise to the appearance of novel resistance mechanisms.